Mechanical characteristics of concrete containing basalt fiber and recycled aggregate. Issue 1 (November 2021) - Hemant,; Sharma, Rachit; Thakur, Ankush; Aditya, Tiwary Kumar
Abstract: The potential of construction waste as an alternative to the constituents of concrete has been generally examined to demonstrate their utility and ensure the climate and/or environment of its otherwise ill effects. The mechanical characteristics of concrete are investigated to comprehend its behaviour under compressive, tensile, and flexural loads. This experimental study investigates the effect of supplanting proportions of river aggregates with waste coarse aggregates in addition to the effect of basalt fiber additions on concrete mixes with (25 and 50%) substitutions of recycled waste coarse aggregates (RWCA). The workability of concrete mixes was negatively affected with recycled aggregates and/or basalt fiber inclusions. Using recycled aggregates with 25 and 50% replacements decreases the strength of concrete. On utilizing discrete proportions of basalt fiber with natural coarse aggregates, the strength was higher as compared to control mix however increasing the percentage of basalt fiber from 1% to 3% the compressive strength was reduced. On incorporating additions of basalt fiber with different proportions of RWCA, the strength of concrete was deteriorated as the percentage of fiber was increasing. For natural aggregates, the inclusion of fibers has negative effect on compressive strength however the tensile strength was increased with higher percentage of fibers. The inclusions of fibers to 25% recycled aggregate mixes, split tensile strength was much higher as compared to control mix. It was concluded that addition of basalt fibers provides a viable option to recycle recycled aggregate in concrete production.